Low-frequency sampling for PRx calculation does not reduce prognostication and produces similar CPPopt in intracerebral haemorrhage patients - Santos, Edgar; Diedler, Jennifer; Sykora, Marek; Orakcioglu, Berk; Kentar, Modar; Czosnyka, Marek; Unterberg, Andreas; Sakowitz, Oliver (Acta neurochirurgica, 2011)
The cerebral pressure reactivity index (PRx) correlates with the outcome in intracerebral haemorrhage (ICH) patients and has been used to define an autoregulation-oriented “optimal cerebral perfusion pressure” (CPPopt). PRx has been calculated as a moving correlation coefficient between mean arterial pressure (MAP) and intracranial pressure (ICP) averaged over 5-10 s, using a 2.5- to 5-min moving time window, in order to reflect changes in MAP and ICP within a time frame of 20 s to 2 min. We compared PRx with a different calculation method [low-frequency PRx (L-PRx)], where rapid fluctuations of MAP and ICP are cancelled (waves with frequencies greater than 0.01 Hz).